ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN MASYARAKAT TERHADAP PROTOKOL KESEHATAN COVID-19 - Halimatuzzahro', Fitria; Himma, Fariha Naharul; Buamona, Regita Sania Ardhia (PATTIMURA UNIVERSITY, 2021)
COVID-19 (Coronavirus Disease-2019) is an infectious disease caused by a new variant of coronavirus. Currently, COVID-19 is declared as a pandemic in many countries in the world, including Indonesia. Hence, Indonesian government has declared an emergency status of COVID-19 in 2020. Based on that declaration, there is a mandatory implementation of health protocols to overcome the pandemic. Even so, there are some people who ignores it. Based on that situation, this study aims to determine the factors affecting the level of community obedience of health protocols. To do this study, data was analyzed using factor analysis by involving eight variables. The result shows that there is two factors, named factor of perception about COVID-19 and factor of perception about health protocols. Factor of perception about COVID-19 involves four variables, such as knowledge variable , trust in government , perceived susceptibility , and perceived severity . Meanwhile, factor of perception about health protocols also involves four variables, such as perceived benefit , perceived barrier , cues to action , and clear information .